New model for ecological assessment of comminution process in energy biomass processing chain - Kruszelnicka Weronika (E3S Web of Conferences, 2020)
Acquiring energy contained in the biomass structure requires its prior appropriate preparation. These treatments require some energy inputs, which significantly affects the reduction of the energy and environmental balance in the entire life cycle of energy biomass processing chain. In connection with the above, the aim of the work was to develop a methodology for ecological assessment of biomass grinding in the processing chain for energy purposes. The research problem was formulated as follows: is it possible to create an assessment model that takes into account the environmental inputs and benefits of the grinding process of biomass intended for further energy use (combustion); how the control variables of the grinding machine affect the ecological evaluation of the process. In response to the research problem, the original index of ecological assessment of the biomass grinding process was developed. The model was verified by assessing the process of rice and maize grinding on a real object - a five-disc mill, for various settings of grinding discs speed. It was found that the developed ecological assessment model allows comparison of grinding processes and indication of the process with a more favorable CO2 emission balance and its values depend on the control parameters of the mill.